2021
DOI: 10.1088/1361-6595/abf31f
|View full text |Cite
|
Sign up to set email alerts
|

Streak investigations of the dynamics of subnanosecond discharge developing in nitrogen at a pressure of 6 atm with the participation of runaway electrons

Abstract: The results of an investigation of a self-sustained subnanosecond discharge in nitrogen at a pressure of 6 atm are presented. A high voltage pulse with a front of approximately 770 ps at the level of 0.1-0.9 in amplitude was applied to the studied gas gap. In this case, the voltage rise rate in the discharge gap at the prebreakdown stage was 1.45 × 10 14 V s −1 . A breakdown occurs at the end of the front of the voltage pulse. The cathode geometry used provided a 3.3-fold enhancement of an electric field in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 70 publications
0
7
0
2
Order By: Relevance
“…If the micro-protrusion experiences an electrical explosion or it is destructed under the impact of the electric field, the emission of FE electrons is eliminated [20,32]. The explosive electron emission (EEE) process can be divided into two stages that, the initial stage involves the heating of metal in the solid state through FE current with the metal density changes slightly, and then the explosion itself occurs (second stage) [51].…”
Section: Fementioning
confidence: 99%
See 1 more Smart Citation
“…If the micro-protrusion experiences an electrical explosion or it is destructed under the impact of the electric field, the emission of FE electrons is eliminated [20,32]. The explosive electron emission (EEE) process can be divided into two stages that, the initial stage involves the heating of metal in the solid state through FE current with the metal density changes slightly, and then the explosion itself occurs (second stage) [51].…”
Section: Fementioning
confidence: 99%
“…Without external pre-ionization sources, diffuse discharge can also be generated and propagate as the ionization wave under extreme field enhancement near the sharpended electrode [15][16][17][18]. Runaway electrons (RAEs) are widely observed in a pin-to-plate geometry (with the pin as the cathode), and are thought to have a decisive effect on the breakdown process and the spatial structure of the discharge [19][20][21]. Furthermore, the photoionization produced by vacuum ultraviolet (VUV) radiation is responsible for the appearance of seed electrons ahead of the discharge front and is thought to play a critical role during the discharge inception [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the field emission current density and the impact ionization coefficient depend exponentially on the electric field. In [28], at the initial stage of development, the discharge has a volumetric form initiated by RAEs, which later turns into a spark (see this article and [25,26,88]). Nitrogen is a molecular gas with a large number of possible electronically excited states.…”
Section: Factors Limiting the Pulse Breakdown Voltage At Hydrogen Pre...mentioning
confidence: 99%
“…In [25,[84][85][86][87][88], using the method of high-speed streak photographic recording, the glow accompanying a subnanosecond discharge in nitrogen in the pressure range from 4.5 atm to 40 atm was investigated. It was shown that a volume discharge is almost instantaneously ignited in the discharge gap, which then passes into the spark stage.…”
Section: Factors Limiting the Pulse Breakdown Voltage At Hydrogen Pre...mentioning
confidence: 99%
See 1 more Smart Citation